Does lipopolysaccharide-based neuroinflammation induce microglia polarization? - Hernandez Baltazar, Daniel; Nadella, Rasajna; Barrientos Bonilla, Abril; Flores Martínez, Yazmin; Olguín, Abraham; Heman Bozadas, Paola; Rovirosa Hernández, María; Cibrián Llanderal, Iliana (Folia Neuropathologica, 2020)
Lipopolysaccharide (LPS) is a potent immunogen when administered locally and/or systemically. The peripheral immunization with LPS could contribute to the progression of neurological diseases because a strong link between neuroinflammation and dopaminergic degeneration has been found. The switch between the survival and neuronal death in substantia nigra could be related to M1 (neurotoxic) and M2 (neuroprotective) microglia phenotypes. In this review, we present the current findings about microglia roles, biomarkers, and natural or synthetic immune modulators determined in the LPS-based murine model.